A Child Diagnosed With Treatment-Resistant Polyarteritis Nodosa: Can the Clinical Diagnosis Be Different? - Demet ALAYGUT; Caner ALPARSLAN; Elif Perihan ÖNCEL; Fatma MUTLUBAŞ; Tunç ÖZDEMİR and Önder YAVAŞCAN and Belde KASAP DEMİR (Archives of Rheumatology, 2019)
Polyarteritis nodosa (PAN) is a necrotizing systemic vasculitis involving the wall of small and medium sized arteries. The histological aspect is defined by the presence of fibrinoid necrosis and an infiltrate rich in neutrophil polynuclears in the artery wall and rare granulomas. CECR1 (Cat Eye Syndrome Chromosome Region 1) gene mutation causing adenosine deaminase 2 (ADA2) deficiency is also associated with systemic inflammation, vasculopathy, and frequently PAN. Strokes, neurological involvement, and gastrointestinal involvement have poor prognosis in the cases with ADA2 deficiency particularly in early stage. In this article, we report a 17-year-old male patient diagnosed with PAN who had severe gastrointestinal system involvement that was resistant to intensive and conventional immunosuppressive treatment and showed a fatal course despite the emergency surgical intervention. After the patient was exitus, he was detected to have a heterozygous mutation (V276A) of familial Mediterranean fever (FMF) and also a homozygous ADA2 mutation. The aim of this article is to highlight that ADA2 deficiency may be present in treatment-resistant PAN cases who apply due to severe systemic involvement. In this case, accompanying FMF mutation was also observed.